The Music of Wagner in Toronto before 1914 - Morey, Carl (Canadian University Music Review / Revue de musique des universités canadiennes)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 1998)
Wagner's music was first heard in Toronto in the 1860s, and in the years before 1914 it achieved extraordinary popularity. Orchestral and vocal excerpts became standard repertoire and the city enjoyed performances conducted by such notable Wagnerians as Walter Damrosch and Anton Seidl and other visitors, as well as by local musicians. There were enthusiastic local Wagnerians such as the conductors Herbert Torrington and Frank Welsman, and the pianist W. Waugh Lauder who had a personal association with Wagner through his teacher, Franz Liszt. Fully staged performances were rarer and depended entirely on touring companies, but nevertheless there were productions of Der fliegende Holländer, Tannhäuser, Lohengrin, Die Walküre, and Parsifal.